Improving Students' Understanding Of Prevention And Eradication Of Illegal Drug Use And Abuse - Azwar, Azwar; Dhika, Veron (CV. Pustaka An Nur, 2025)
Drug abuse poses a significant threat to the younger generation. National Narcotics Agency (2023) data indicates 312,000 users among students. This community service initiative aims to enhance the understanding and preventive capacity of students at Mercubaktijaya Padang University regarding the dangers of drugs through socialization of the P4GN program (Prevention and Eradication of Drug Abuse and Illicit Trafficking), supporting the realization of a BERSINAR Campus (Drug-Free Campus). The method utilized an educational intervention based on interactive lectures and participatory discussions, involving 150 students. Effectiveness was evaluated using a one-group pretest-posttest design with standardized questionnaires, analyzed statistically using a paired sample t-test. Results indicated a significant increase in knowledge (p<0.05). The proportion of participants with